Desnaturalização dos sistemas fluviais urbanos: o caso do Canal da Costa e do Canal Bigossi, Vila Velha (ES) . - Sartório, Marcus Vinícius Oliveira (2018)
Notably, urban rivers have been affected by urban sprawl in big cities. Despite the intimate relationship between cities and rivers over time, the conflicts generated by urbanization have brought down the value of their presence, and they have come to be seen as an obstacle to the city growth. What was observed in the city of Vila Velha in the state of Espírito Santo was the complete denaturalization of the river system in detriment to the expansion of the city and the maintenance of the flood events that occur in the plain where it is located. In this scenario, the central objective of the research is to investigate the evolutionary process of denaturation of the fluvial system of the Costa and Bigossi channels based on a systemic approach, identifying the relationship between the growth of the city of Vila Velha and the modifications made in the channels and in its drainage basin. Under the systemic vision we sought to identify the geomorphological aspects that characterize the study area, and the elements inserted by the man, responsible for the modification of the initial system. These new elements in the fluvial dynamics were identified as the channeling of the rivers, the creation of new canals and the waterproofing of the drainage basin. It was verified that the modifications made in the rivers and the plain not only disregarded the natural dynamics of the environment to which they are located, but also, they were responsible for the complete loss of characteristics of these areas, transforming the state of equilibrium of the system which consists of a floodplain, creating an environment more vulnerable to flooding